Several years’ observation of a suppurating pancreatic cyst, which eventually turned out to be a cancer – case study - Chorąży, Marek; Jabłońska, Dorota; Skrzypek, Elżbieta; Nasiek-Palka, Anna (Contemporary Oncology/Współczesna Onkologia, 2009)
The authors describe the observation, attempts of treatment and diagnostic tests of a huge suppurating pancreatic cyst diagnosed in a 48-year-old patient, in which after four years features of a malignant cancerous process were found. Despite repeated external drainage under ultrasound control and surgical treatment no satisfactory therapeutic effects were obtained. Segments taken repeatedly for histopathological examination did not reveal any pathological hyperplasia of the tissue. Cancer markers which were examined showed proper values at the initial stages. Only after 4 years was a change of the cyst’s picture during ultrasound tests observed; metastatic lesions in the liver were found, segments taken from both the cyst and the liver revealed an adenoma, and the examination of the cancer markers proved their pathological values. On the basis of our own previous observations of similar cases it is supposed that we dealt with a malignant transformation which appeared during the illness, and not with a cancerous process from the very beginning. It seems that one of the criteria implying a change of the pancreatic cyst’s character from benign to malignant may be the evolution of the cyst’s picture during the ultrasound of the pancreas. The work aims to present diagnostic difficulties of such cases.